Some strategies to improve the learning process - Beatriz Amante García; María Martínez Martínez (Journal of Technology and Science Education, 2017)
This last issue of JOTSE’s volume 7 focuses on the diverse teaching/learning strategies being carried out in several universities worldwide. In this sense, our current issue reflects that no matter the continent nor the subject being taught the teaching staff is always concerned with students’ learning process in their classrooms and that is why they do research on a wide range of strategies that could possibly favour such learning process as well as motivate their students.